Administrative Accountability of the Indonesian Government in Environmental Management for Tourism Development - Leonito Ribeiro; I Nyoman Gede Sugiartha (Fakultas Hukum, Universitas Warmadewa, 2022)
A good and healthy living environment is the right of every Indonesian citizen as mandated in Article 28H of the 1945 Constitution of the Indonesian Republic. Unwise environmental management will aggravate the degradation of the environment, and therefore, improving the protection and management of the environment becomes necessary. Government accountability in environmental protection and management is a part of their public service function to ensure that people have a good and healthy environment. Thus, the puposes of this research are to examine the administrative accountability in environmental management for tourism development and to find a way to resolve legal consequences the government can face for its decision in environmental management in tourism development. This research is normative and empirical legal research and applied several approaches: statute approach, conceptual approach, philosophical approach, historical approach, comparative approach, case approach, and cultural approach based on local wisdom. The results show that the protection and management of the environment are efforts to take on a difficult responsibility, making environmental degradation more evident. Therefore, administrative law enforcement is the first step for the government to enforce the law immediately for environmental protection. The enforcement of administrative law and the integration of the values that grow in society in protecting and preserving the environment is ideal forms of wise environmental protection and management to realize tourism development. However, if the government fails to protect and manage the environment in developing tourism, the government can be held administratively accountable.